Impact of Farm Roads on the Accessibility of Farmers in Olas Hamlet, Lokki Village, Huamual District, West Seram Regency - Faida, Nur; Lasaiba, Mohammad Amin; Riry, Johan (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
This study aims to determine the influence between farmer roads, accessibility, the impact of farmer roads, and participation on farmer satisfaction. The research method used is quantitative research using multiple linear regression analysis techniques to predict the influence of free variables on variables bound to samples in the study of 24 respondents. The results of this study show that the independent variable (X), namely farmer roads, accessibility, the impact of farmer roads, and participation, affects the dependent variable (Y), namely farmer satisfaction, which is determined based on significant values in the results of multiple linear regression analysis obtained values of 0.00 < 0.05, which means that variable X affects variable Y. Based on the calculated t value, each variable has a positive influence determined based on the acquisition of values, namely the value of X1 t count 2,197 > the value of t table 2,093, the value of X2 t count 3,028 > the value of t table 2,093, the value of X3 t count 2,518 > the value of t table 2,093, and the value of X4 t count 3,952 > the value of t table 2,093, so it can be concluded that the independent variable (X) has a positive influence on the dependent variable (Y).